Effects of ocean acidification and eutrophication on the growth and photosynthetic performances of a green tide alga Ulva prolifera - Cai, Jianping; Ni, Jiaxuan; Chen, Zeyu; Wu, Shiqi; Wu, Ruijie; He, Chuang; Wang, Jinguo; Liu, Yili; Zhou, Wei; Xu, Juntian (Frontiers in Marine Science, 2023)
With the impact of fossil fuel burning and industrialization, atmospheric CO2 concentration will reach about 1000 ppmv in 2100, and more and more CO2 will be absorbed by ocean, resulting in ocean acidification. The Chinese coastal waters are showing unexpectedly high levels of acidification due to a combination of global ocean acidification and severe regional eutrophication, which is caused by natural accumulation or human activities such as aquacultural tail water input, potentially affecting macroalgal blooms. However, little is known about the combined effects of ocean acidification and entrophication on the eco-physiology of bloom-forming macroalgae. This study investigated Ulva prolifera, a dominant species causing green tide in the South Yellow Sea, and explored its growth and physiological responses under the combination conditions of ocean acidification and enriched nutrients. In this study, U. prolifera thalli were cultured under two CO2 conditions (air and 1000 μatm) and two nutrient conditions (High Nutrient, HN, 135 μmol L-1 N and 8.5 μmol L-1 P; Normal Nutrient, NN, 27 μmol L-1 N and 1.7 μmol L-1 P). The results showed that eutrophication conditions obviously enhanced the relative growth rate and photosynthetic performance of U. prolifera. Elevated pCO2 had no significant effect on U. prolifera growth and photosynthetic performance under normal nutrient conditions. However, under eutrophication conditions elevated pCO2 inhibited U. prolifera growth. Moreover, eutrophication conditions markedly improved the contents of chlorophyll a, chlorophyll b and nitrate reductase activity and inhibited the soluble carbohydrate content, but elevated pCO2 had no significant effect on them under nutrient-replete conditions. In addition, elevated pCO2 significantly reduced the carotenoid content under eutrophication conditions and had no effect on it under normal nutrient conditions. These findings indicate that seawater eutrophication would greatly accelerate U. prolifera bloom, which may also be suppressed to a certain extent by ocean acidification in the future. The study can provide valuable information for predicting the future outbreaks of U. prolifera green tide in nearshore regions.